[Man Mowing Lawn in Akureyri] - Streng, Evelyn Fiedler (1975)
Photograph of a man mowing his lawn in Akureyri, Iceland. The man wears a white shirt with black pants and a black hat. He stands on a steep hill behind a dark, wired fence. A blue roof and a white building with a red roof are visible behind a dark green hill to the right. Two, pointed roofs sit at the front of the white building. A white building with red trimming and roofs. A fjord surrounded by rounded, dark green mountains are visible in the background.